Clinical research Is there a gender difference in associates of adolescents’ lifetime illicit drug use in Tehran, Iran? - Khooshabi, Katayoon; Forouzan, Setareh-Ameneh; Ghassabian, Akhgar; Assari, Shervin (Archives of Medical Science, 2010)
Introduction: Information regarding gender differences in drug use of adolescents is essential for designing gender-specific drug prevention policies. This study was conducted in high school students in Tehran, Iran, in 2007. Here, we report the gender differences in lifetime prevalence as well as psychosocial associates of drug use. Material and methods: This was a gender analysis of the data collected in a drug use survey conducted in a random sample of high school adolescents (573 boys and 551 girls) in Tehran, Iran, 2007. Demographic characteristics, parental and peers’ substance use, school performance, religious beliefs, attachment, self-esteem and emotional intelligence (EI) were entered in logistic regression analyses to predict the lifetime illicit drug use in boy and girls, separately. Results: Boys were more likely to report lifetime illicit drug use than girls (10.1% vs. 6.4%, p = 0.023). Differences in the risk profile associated with lifetime illicit drug use by gender included history of substance use in the family, higher score of attachment, and having an employed mother as predictors of substance use in boys, but not girls. Conclusions: Understanding this gender difference in predictors of lifetime use of illicit drugs in high school adolescents facilitates the design of gender-sensitive drug use preventive programmes. It seems that family variables may have more value in prevention of illicit drug use in male adolescents.